A Comparative Study of the T Cell Stimulatory and Polarizing Capacity of Human Primary Blood Dendritic Cell Subsets - Sittig, Simone P. (Mediators Inflamm, 2016)
Dendritic cells (DCs) are central players of immune responses; they become activated upon infection or inflammation and migrate to lymph nodes, where they can initiate an antigen-specific immune response by activating naive T cells. Two major types of naturally occurring DCs circulate in peripheral blood, namely, myeloid and plasmacytoid DCs (pDCs). Myeloid DCs (mDCs) can be subdivided based on the expression of either CD1c or CD141. These human DC subsets differ in surface marker expression, Toll-like receptor (TLR) repertoire, and transcriptional profile, suggesting functional differences between them. Here, we directly compared the capacity of human blood mDCs and pDCs to activate and polarize CD4(+) T cells. CD141(+) mDCs show an overall more mature phenotype over CD1c(+) mDC and pDCs; they produce less IL-10 and more IL-12 than CD1c(+) mDCs. Despite these differences, all subsets can induce the production of IFN-γ in naive CD4(+) T cells. CD1c(+) and CD141(+) mDCs especially induce a strong T helper 1 profile. Importantly, naive CD4(+) T cells are not polarized towards regulatory T cells by any subset. These findings further establish all three human blood DCs—despite their differences—as promising candidates for immunostimulatory effectors in cancer immunotherapy.